What determines the location choice of multinational firms in the ICT sector? - Iulia Siedschlag; Xiaoheng Zhang; Donal Smith (The Economic and Social Research Institute (ESRI), 2009)
We analyse the location decisions of 8,468 foreign affiliates in the Information and Communication Technologies (ICT) sector established in 224 regions in the European Union over the period 1998-2008. Our results suggest that on average, the location probability of foreign affiliates in ICT manufacturing and services increases with market size, market potential, the presence of other foreign-owned firms in the ICT sector, human capital, income tax, and decreases with the corporation tax rate. In addition, in the case of foreign affiliates in ICT services, the innovation intensity in the ICT sector has a positive effect on the location probability. We find that relevant geographical structures for the location decision are different for multinationals with a parent firm in the European Union and the United States.
Keywords: 330; foreign direct investment; Information and Communication Technologies; location choice; conditional logit; nested logit; Multinationales Unternehmen; IT-Industrie; Betriebliche Standortwahl; Diskrete Entscheidung; Logit-Modell; EU-Staaten